SEARCHING FOR ALTERNATIVE POSSIBILITIES FOR IMPROVING THE LIVING CONDITIONS OF CITY RESIDENTS THROUGH MODIFICATIONS TO TRAFFIC FLOW - Simiński, Przemysław; Płochocki, Patryk; Kravcov, Alexander (Management and Administration Journal, 2024)
The identification of best practices in traffic organization and road infrastructure in urban agglomerations indicates their low effectiveness in terms of traffic flow. Through the acquisition and synthesis of available knowledge, this article aims to foreground effective organizational and technical concepts that will help efficiently reduce traffic congestion in urban agglomerations. A modern city or urban area is a system of interconnected elements that influence people’s quality of life; influenced, among other things, by the accessibility of amenities or urban space related to the effort required for mobility, often involving emotional, temporal, and financial costs. People’s movement encounters many limitations related to urban area management. The conducted theoretical research indicates that any effective reduction of traffic congestion in urban agglomerations would require a combination of different organizational and technical solutions. Best practices in traffic organization and road infrastructure include the development of public transport networks, the implementation of intelligent transport systems, variable road pricing, and urban planning that considers traffic flow. Of course, radical restrictions on road traffic in cities are also possible through the utilization of various technical and organizational solutions, such as promoting alternative means of transportation.